The Correlation Between Serum Homocysteine Levels and Hypothyroidism: a 1-Year Case Control Study - Dr. Anjali R. Metgudmath (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Thyroid hormones have significant effects on lipid metabolism and homocysteine levels. Decrease in thyroid hormone levels may alter the homeostasis of lipid metabolism and homocysteine levels. Objectives To study the incidence of hyperhomocysteinemia and hypercholesterolemia in patients with hypothyroidism, and to find out the correlation of homocysteine with cholesterol levels, thyroid hormones and thyroid-stimulating hormone (TSH) in newly detected hypothyroid patients. Methods In this prospective case-control study, 30 hypothyroid patients (case group) and 30 euthyroid controls were included. Patients with a TSH level >4.78 mIU/mL were considered in the case group and those with TSH level <4.78 mIU/mL were included in the control group. Cases and controls were matched on the basis of age, sex, and body mass index. Levels of TSH, free T3 andT4, fasting serum homocysteine, and total cholesterol were investigated in both case and control groups. The data were statistically analysed with Independent t-test and Pearson’s correlation method by SPSS 20.0. Results Compared to controls, significant increase in serum homocysteine levels was observed in in hypothyroid group (P = 0.0064). Serum total cholesterol levels were significantly higher in hypothyroid group when compared with control (P = 0.0066). Correlation of serum homocysteine levels with the levels of TSH, free T3 and T4, and serum cholesterol levels were statistically not significant in both hypothyroid group. Conclusion We observed a significant increase in levels of homocysteine and total cholesterol levels in hypothyroid group when compared with control. Hyperhomocysteinemia and increased cholesterol levels can contribute to cardiovascular risks. We recommend screening of serum homocysteine levels in hypothyroid patients to detect atherosclerosis and cardiovascular diseases.